A comparison of procedural success rate and long-term clinical outcomes between in-stent restenosis chronic total occlusion and de novo chronic total occlusion using multicenter registry data - Lee, Seung Hun (Clin Res Cardiol, 2019)
BACKGROUND: There have been little data about outcomes of percutaneous coronary intervention (PCI) for in-stent restenosis (ISR) chronic total occlusion (CTO) in the drug eluting stent (DES) era. This study aimed to compare the procedural success rate and long-term clinical outcomes of ISR CTO and de novo CTO. METHODS AND RESULTS: Patients who underwent PCI for ISR CTO (n = 164) versus de novo CTO (n = 1208) were enrolled from three centers in Korea between January 2008 and December 2014. Among a total of ISR CTO, a proportion of DES ISR CTO was 79.3% (n = 130). The primary outcome was major adverse cardiac events (MACEs); a composite of all-cause death, non-fatal myocardial infarction (MI), or target lesion revascularization (TLR). Following propensity score-matching (1:3), the ISR CTO group (n = 156) had a higher success rate (84.6% vs. 76.0%, p = 0.035), mainly driven by high success rate of PCI for DES ISR CTO (88.6%), but showed a higher incidence of MACEs [hazard ratio (HR): 2.06; 95% confidence interval (CI) 1.37–3.09; p < 0.001], mainly driven by higher prevalence of MI [HR: 9.71; 95% CI 2.06–45.81; p = 0.004] and TLR [HR: 3.04; 95% CI 1.59–5.81; p = 0.001], during 5 years of follow-up after successful revascularization, as compared to the de novo CTO group (n = 408). CONCLUSION: The procedural success rate was higher in the ISR CTO than the de novo CTO, especially in DES ISR CTO. However, irrespective of successful revascularization, the long-term clinical outcomes for the ISR CTO were significantly worse than those for the de novo CTO, in terms of MI and TLR. GRAPHIC ABSTRACT: [Image: see text]